Epidemiology and genetics of CTX-M extended-spectrum β-lactamases in Gram-negative bacteria - Zhao, Wei-Hua (Informa Healthcare, 2013)
CTX-M enzymes, the plasmid-mediated cefotaximases, constitute a rapidly growing family of extended-spectrum β-lactamases (ESBLs) with significant clinical impact. CTX-Ms are found in at least 26 bacterial species, particularly in Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis. At least 109 members in CTX-M family are identified and can be divided into seven clusters based on their phylogeny. CTX-M-15 and CTX-M-14 are the most dominant variants. Chromosome-encoded intrinsic cefotaximases in Kluyvera spp. are proposed to be the progenitors of CTX-Ms, while ISEcp1, ISCR1 and plasmid are closely associated with their mobilization and dissemination.